Samenloop in The Form of A Criminal Act of Joint Persecution or Participation in The Victim of Wrongful Arrest Committed by The Police Implications for Justice - Tubagus Ahmad Ramadan; Rineke Sara (Yayasan Adra Karima Hubbi, 2024)
The phenomenon of samenloop in cases of wrongful arrest by police officers in Indonesia poses serious implications for justice and public trust. This issue arises from structural and cultural weaknesses in the policing system, leading to persecution, abuse of authority, and falsification of evidence against victims. This study aims to analyze the factors causing samenloop and its impact on victims and the criminal justice system. Using a qualitative approach, the research examines 50 documented cases of wrongful arrest from 2019 to 2023, identifying patterns of violations and systemic shortcomings. The findings reveal that samenloop frequently stems from inadequate accountability mechanisms, poor human rights training, and entrenched organizational cultures that enable misconduct. The consequences include psychological harm to victims, erosion of public confidence, and inefficiencies in the justice system. This study concludes that addressing samenloop requires comprehensive reforms, including strengthening legal frameworks, enhancing human rights-based training for police officers, and fostering a culture of accountability within police organizations. These measures are essential to uphold justice and rebuild public trust in law enforcement institutions.